REPRESENTASI PERUNDUNGAN (BULLIYING) PADA NOVEL DAN HUJAN PUN BERHENTI KARYA FARIDA SUSANTY: PENDEKATAN SOSIOLOGI SASTRA - Aidi Fitri; Lamria Naibaho; Seriana -; Friska Ria Sitorus (Jurnal Bahasa Indonesia Prima (JBIP), 2023)
This research is motivated by the problem of rampant bullying that is currently happening in the community without exception, with the rampant bullying that often occurs among students, seen explicitly by researchers. Therefore, researchers are interested in exploring bullying. Based on the description above, it is necessary to conduct research. The writer is interested in analyzing the representation of bullying in the novel, "And the Rain Stopped by Farida Susanty, through a literary, sociological approach." The researcher categorized into sub-problems to be more focused: (1) What are the forms and impacts of bullying in the novel "And the Rain Stopped by Farida Susanty"? (2) What are the factors or causes of bullying in the novel "And the Rain Stopped by Farida Susanty"?. The research method is descriptive qualitative. The research data are in the form of words, phrases, and sentences that contain representations of bullying in the novel by Farida Susanty, namely what forms of bullying, factors or causes of bullying, and the impact of bullying. The novel contains categories of verbal/verbal bullying and psychological and physical bullying.